PENGEMBANGAN MEDIA BUKU CERITA BERGAMBAR BERBASIS KEARIFAN LOKAL SASAK UNTUK SISWA KELAS IV SDN I BUWUN MAS - Permani, Wulandari Julia; Saputra, Heri Hadi; Sobri, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to develop picture story book media based on local Sasak wisdom that is valid and practical in Indonesian language learning for fourth grade students at SDN I Buwun. This research is a type of Research and Development (R&D) research using the ADDIE analysis, design, development, implementation and evaluation development models. The data collection techniques used were validation questionnaires from material experts, media experts and student response questionnaires as well as documentation in the form of photos of the research process at SDN I Buwun Mas. This research was conducted at SDN I Buwun Mas using material and media expert validation sheet instruments as well as student response questionnaires. The results of this research show that picture story book media based on Sasak local wisdom received a percentage of 85% with very valid criteria from material experts, a percentage of 80% with valid criteria from media experts, a percentage of 91.3% with very practical criteria from student responses in the trial. small group, percentage 93.3% with very practical criteria from student responses in large group trials. Therefore, it can be concluded based on the research results that the development of picture story book media based on Sasak local wisdom in class IV Indonesian language learning was carried out through five main stages, namely the analysis stage, design stage, development stage, implementation stage and evaluation stage and based on the results of data analysis obtained, the picture story book media based on Sasak local wisdom can be declared valid and practical.